ANALISIS PENURUNAN WAKTU SETUP DENGAN MENGGUNAKAN SINGLE MINUTE EXCHANGE OF DIE UNTUK MENINGKATKAN PRODUKTIVITAS PADA AUTOMATIC MOULDING MACHINE - Dandy Silva; Widya Setiafindari (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
PT XYZ is a company that has been engaged in metal casting for a long time. This company produces products in the form of wingnut spare parts. The production system used is make to order production. The obstacle faced by PT XYZ was that it was found that the setup operation process activity took quite a long time on average 40 minutes. If it continues to occur it will have an impact on delays. With these problems, PT XYZ reduced the setup time to overcome delays in completing the automatic molding machine wingnut product. Utilize the Single minute exchange of die (SMED) method to speed up setup. The SMED approach distinguishes between internal regulatory and external regulatory activities. Adjustment activities that only Internal adjustments can be made while the machine is stopped. The External Setup setup activity can be performed while the machine is running or operating. By switching to external setup instead of internal setup, setup tasks that were completed when the machine was stopped can now be completed while it is running, thereby reducing setup time. the setup operation of all these activities is carried out when the engine is off or the internal setup produces an average of 101 molds. Meanwhile, the setup time after implementing SMED can be reduced to 26.78 minutes or a decrease of 47.61%. This decrease in setup time increases productivity by 2 molds/day and if in a month with 26 working days it can add 59 molds so that in total it can produce 159 molds/month.